Community Participation In Fire Disaster Mitigation In The City Of Banjarmasin - Ramadhani, Ramadhani; Husein, Rahmawati; Zaenuri, Muchamad; Shaddiq, Syahrial (SMARTINDO, 2023)
Very heterogeneous community conditions where urban environmental conditions cause areas to become congested and result in environmental conditions that tend to be slums. City environmental conditions, housing, factories and so on must have good access, in order to avoid hazards that will occur such as the danger of residential fires. The development paradigm that exists in Banjarmasin City, the government's role as a provider of public facilities has changed slightly with the community's efforts to participate in assisting the city government in the community-based fire disaster mitigation process. The purpose of this study was to find out how the form of community participation in mitigating fires in the Malay Village, Central Banjarmasin District, Banjarmasin City. This type of research is a qualitative descriptive research. Data collection techniques in this study, researchers used documentation study techniques, guided interviews and direct observation from the field. The data analysis technique that will be used is descriptive qualitative method. The results of the study show that the presence of the self-help Fire Brigade (BPK) has become the identity of the city both at the national and international levels, as a city of a thousand rivers and a city of a thousand firefighters. Community participation is quite diverse and very innovative in reducing the risk of residential fire disasters in Malay sub-districts. Interestingly, the presence of the self-help Fire Brigade (BPK) is unpaid, the members on duty do not get a salary in carrying out this humanitarian task, their participation is sincere and voluntary